Problematizing law, rights, and childhood in Israel/Palestine - Viterbo, Hedi (Cambridge : Cambridge University Press, 2021)
In this book, Hedi Viterbo radically challenges our picture of law, human rights, and childhood, both in and beyond the Israel/Palestine context. He reveals how Israel, rather than disregarding international law and children's rights, has used them to hone and legitimize its violence against Palestinians. He exposes the human rights community's complicity in this situation, due to its problematic assumptions about childhood, its uncritical embrace of international law, and its recurring emulation of Israel's security discourse. He examines how, and to what effect, both the state and its critics manufacture, shape, and weaponize the categories 'child' and 'adult.' Bridging disciplinary divides, Viterbo analyzes hundreds of previously unexamined sources, many of which are not publicly available. Bold, sophisticated, and informative, Problematizing Law, Rights, and Childhood in Israel/Palestine provides unique insights into the ever-tightening relationship between law, children's rights, and state violence, at both the local and global levels.
Conceptual and theoretical foundations -- Casting the first stone : the Israeli legal system, its human rights critics, and their approaches to young Palestinians -- The age of governing : young age as a means of control -- Boundary governance : amending childhood and separating Palestinians -- Stolen childhood : voice, loss, and trauma in human rights reports -- Sights of violence : childhood in the visual battlefield -- Infantilization and militarism : soldiers as children, children as soldiers -- Unsettling children : Israeli law and settlers' childhood.
Title from publisher's bibliographic system (viewed on 05 Aug 2021).
Keywords: Children -- Legal status, laws, etc. -- Israel; Arab-Israeli conflict -- Law and legislation; Children -- Legal status, laws, etc. -- Gaza Strip; Children -- Legal status, laws, etc. -- West Bank